ANALISIS KEPENTINGAN INDUSTRI MEDIA TELEVISI DI INDONESIA - Felisianus Efrem Jelahut; Mariana Agusta Noya Letuna (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
This research is in the form of an analysis of the interests of the television media industry in Indonesia. Highlighted in this study are TV stations operating under industrial ownership, namely Metro TV (Media Group), TV One (Viva Media Asia), Kompas TV (Gramedia Media Nusantara), RCTI (MNC), and Indosiar (Elang Mahkota Teknologi). The purpose of this study was to determine the existence of the interests of the television media. This study uses a qualitative method with a case study approach. The results show that the five TV stations, each owned by five private television media industries in Indonesia, have public, political, and business economic interests.